Effect of the decision making process in the speed of defensive displacement in handball - Rivilla, J.; Lorenzo, J.; Ferro, A.; Sampedro, J. (EHF Scientific Conference 18.-19.11.2011, Wien, Österreich, 2011)
The present study aim to analyze the influence of the decision making process in the speed of defensive specific displacement in professional team handball players. The analysis of differences stated significantly major values in the test without decision making process that with opposition. The results allowed to confirm that the decision making process had a negative effect on the speed of defensive displacement.